2010
DOI: 10.1002/esp.2099
|View full text |Cite
|
Sign up to set email alerts
|

Geometric characteristics and evolution of a tidal channel network in experimental setting

Abstract: This paper reports on a laboratory study that aims to reproduce a tidal channel network, in order to enhance the understanding of the morphodynamic evolution of the channel characteristics as the network expands and finally reaches equilibrium. A high-resolution laser system scanned the bed topography at different time steps creating multiple digital elevation models of the channel network. Two hundred and seventy individual channel segments are analyzed and cross-correlated in terms of their width, depth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 54 publications
1
46
0
Order By: Relevance
“…Some studies suggest tidalchannel development to be the result of depositional rather then erosional processes [e.g., Redfield, 1965;Hood, 2006], whereas others consider erosion as the dominant process [e.g., Fagherazzi and Sun, 2004;Perillo et al, 2005;D'Alpaos et al, 2005D'Alpaos et al, , 2007bVlaswinkel and Cantelli, 2011]. In the erosional scenario, differential erosion drives the evolution: Network configuration is driven by local excess in the bed shear stress compared to the critical threshold for sediment motion, as modelled in this experimental context.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Some studies suggest tidalchannel development to be the result of depositional rather then erosional processes [e.g., Redfield, 1965;Hood, 2006], whereas others consider erosion as the dominant process [e.g., Fagherazzi and Sun, 2004;Perillo et al, 2005;D'Alpaos et al, 2005D'Alpaos et al, , 2007bVlaswinkel and Cantelli, 2011]. In the erosional scenario, differential erosion drives the evolution: Network configuration is driven by local excess in the bed shear stress compared to the critical threshold for sediment motion, as modelled in this experimental context.…”
Section: Discussionmentioning
confidence: 87%
“…These models deepen our understanding of tidal network growth, otherwise analyzed solely on the basis of field observations and related conceptual models [e.g., Redfield, 1965;Allen, 1997;Perillo et al, 2005;Hood, 2006;D'Alpaos et al, 2007b;Hughes et al, 2009]. In two cases tidal network initiation and development have been addressed with physical models [Stefanon et al, 2010;Vlaswinkel and Cantelli, 2011]. These studies showed that laboratory experiments can successfully model tidal network dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…However, we also realize that field observations can be restrained by many practical factors such as severe local environmental conditions (e.g., extreme weather), human interventions and limited availability of advanced measurement facilities. In this regard, controlled laboratory experiments may be another promising alternative to further the understanding of intertidal flat morphodynamics (Stefanon et al, 2010;Vlaswinkel and Cantelli, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…are typically not well preserved (Dalrymple and Choi, 2007). Recent studies demonstrated that physical experiments are capable of reproducing several typical tidal features, such as ebb deltas (Kleinhans et al, 2012), tidal channel networks (Stefanon et al, 2010;Vlaswinkel and Cantelli, 2011) and tidal estuaries (Kleinhans et al, 2014a). Recent studies demonstrated that physical experiments are capable of reproducing several typical tidal features, such as ebb deltas (Kleinhans et al, 2012), tidal channel networks (Stefanon et al, 2010;Vlaswinkel and Cantelli, 2011) and tidal estuaries (Kleinhans et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%